639. Short Course Therapy for Urinary Tract Infections (SCOUT) in Children. (31st December 2020) - Zaoutis, Theoklis; Bhatnagar, Sonika; Black, Stephen I; Coffin, Susan E; Coffin, Susan E; Downes, Kevin J; Fisher, Brian T; Fisher, Brian T; Gerber, Jeffrey; Green, Michael D; Lautenbach, Ebbing; Liston, Kellie; et al.
Abstract: Background: The AAP recommends 7 to 14-days of antimicrobials for the treatment of urinary tract infections (UTIs), one of the most common bacterial infections of childhood. However, most physicians routinely prescribe at least 10 days of therapy. Prior observational studies suggest that courses shorter than 10 days might be effective. Methods: The primary objective was to determine if halting antimicrobial therapy in children who improved clinically after 5 days of therapy (short course therapy) results in a similar failure rate as children who continue antimicrobials for an additional 5 days (standard course therapy). This was a multi-center, randomized, double-blind, placebo-controlled non-inferiority clinical trial of children ages 2 to 10 years with UTI. Subjects treated with 1 of 5 antibiotics (trimethoprim-sulfamethoxazole, amoxicillin-clavulanate, cefixime, cefdinir or cephalexin) were eligible. Children were stratified by presence or absence of fever and were enrolled if they had clinical improvement before Day 5 of treatment. The a priori equivalence interval was set at 0.05 for a one-sided analysis. The primary outcome was development of a symptomatic UTI defined as the presence of symptoms, pyuria, and a positive urine culture. The Intent-to-Treat population included children who took at least one dose of study medication. Results: A total of 693 children were randomized, 345 to short course and 348 to standard course. Median age was 4 years old (IQR; 2-6), 652 (96.3%) were female and 255 were febrile (37%). Treatment success rate was 322/336 (96%) for short course and 326/328 (99%) for standard course. The 95% upper CI limit for the difference was 0.054. Treatment failure was not related to age group, fever at presentation, antibiotic type, or study site. There were no significant differences between groups the in the rates of adverse events, recurrent infection, clinical symptoms that may have been related to UTI, or emergent antibiotic resistance. Conclusion: In children aged 2 months to 10 years with UTI, halting antimicrobial therapy in children who had exhibited clinical improvement after 5 days and continuing for an additional 5 days both resulted in high success rates. However, short course was inferior to treatment for 10 days. Disclosures: Kevin J. Downes, MD, Merck, Inc. (Grant/Research Support) Brian T. Fisher, DO, MPH, MSCE, Astellas (Advisor or Review Panel member)Merck (Grant/Research Support)Pfizer (Grant/Research Support)